2013
DOI: 10.1002/jmr.2283
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of serum amyloid A with human cystatin C—assessment of amino acid residues crucial for hCC–SAA formation (part II)

Abstract: Secondary amyloid A (AA) amyloidosis is an important complication of some chronic inflammatory diseases, primarily rheumatoid arthritis (RA). It is a serious, potentially life-threatening disorder caused by the deposition of AA fibrils, which are derived from the circulatory, acute-phase-reactant, serum amyloid A protein (SAA). Recently, a specific interaction between SAA and the ubiquitous inhibitor of cysteine proteases--human cystatin C (hCC)--has been proved. Using a combination of selective proteolytic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Consistent with this idea, several polar/charged ligands of SAA reportedly bind at the CT residues 70–104. These ligands include heparan sulfate that binds to the basic residues from the 83–102 region in mSAA [28]; cystatin C that forms electrostatic interactions with SAA residues 86–104 [31]); and cell receptors such as LOX-1 and CD36 that bind modified lipoproteins [37] (Figs. 2, 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this idea, several polar/charged ligands of SAA reportedly bind at the CT residues 70–104. These ligands include heparan sulfate that binds to the basic residues from the 83–102 region in mSAA [28]; cystatin C that forms electrostatic interactions with SAA residues 86–104 [31]); and cell receptors such as LOX-1 and CD36 that bind modified lipoproteins [37] (Figs. 2, 5).…”
Section: Resultsmentioning
confidence: 99%
“…These include hydrophobic ligands such as HDL and other plasma lipoproteins [711], cell membranes, model liposomes [2325], cholesterol [26] and retinol [14]; charged ligands such as metal ions [27] and heparan sulfate proteoglycans [2830]; and numerous proteins such as cystatin C [31], extracellular matrix proteins [32, 33] and cell receptors. The latter include several G-protein coupled receptors (such as formyl peptide receptor-like 1 and toll-like receptors 2 and 4) and scavenger receptors (SR-BI, CD36, and LOX-1).…”
Section: Introductionmentioning
confidence: 99%
“…3a, b) the potential for hydrophilic domain exposure after HDL binding has suggested regions responsible for fibronectin and laminin binding (aa 39-41 and 29-33, respectively). Residues toward the C-terminus (including aa 70-104) include regions implicated in binding to heparan sulfate (aa 83-102 (Ancsin and Kisilevsky 1999)), cystatin C (11 86-104 (Spodzieja et al 2013)) and receptors LOX 1 and CD36 (Tomita et al 2015). Such interactions could permit SAA-mediated binding and possibly internalization into cells with these receptors for these species.…”
Section: Saa and Lipidsmentioning
confidence: 99%
“…Consecutive structural experiments were performed using selective proteolytic excision and high resolution mass spectrometry (Juszczyk et al, 2009;Maftei et al, 2012;Tian et al, 2007) in order to identify the crucial binding 'hotspots' both in Ab and SAA. Surprisingly, the identified interaction site of Fb is located in the 101 IYAVPWQGTMTLSKSTC 117 hCC fragment (Juszczyk et al, 2009), whereas the identified epitope on SAA is located in 96 FCSFQIY 102 fragment (Spodzieja et al, 2013;Spodzieja et al, 2012). These studies highlight the importance of CysC3 peptide, which according to our experimental results exhibits the tendency to self assemble into amyloid-like fibrils.…”
Section: Cysc2 Cysc3mentioning
confidence: 38%